Analysis of the management of the public expenditure in investment and its incidence on the reduction of the levels of poverty in Peru - Alvarado Tolentino, James Manolo (2018)
Objective: To analyze the incidence of the management of public spending on investment on the reduction of poverty levels in Peru, during the period from 1994 to 2015; Method: A descriptive and explanatory method of correlational design and longitudinal cut study was used. The processing of the indicators was done through the Eviews program. Result and conclusions: The management of public investment improved the quality of the formulation and execution of public investment projects, the SNIP (National System of Public Investment), played an important role in the decentralization process (getting to optimize the articulation of national investment policies with territorial policies, citizen participation, and public accountability within the framework of public administration), the management of public investment achieved poverty reduction, throughout the study period the management of the public spending on investment and poverty levels have an inverse relationship.